Um novo papel para o agente de integração: o estudo de caso do IEL/BA - Lima, Edneide de Oliveira (2006)
The study had as motivation the increasing fidget related to the distortions that compromise the purposes of the curricular training and the organizational dissatisfaction evidenced in the professional exercise regarding the interaction between university and company in Bahia. Considering the agents involved in the process of curricular training, which are the conceding unit; the university, through the professors who authorize and follow the students in the process of curricular training; and the integration agent; it was questioned the distortions that compromise its curricular objectives, generating the questions that guided the study. The objective of this research is to verify if the extension of functions of the integration agent, to guidance and supervision of the curricular training in the organization, would be a mechanism capable to minimize the distortions that compromise this important process of professional formation and to foment greater interaction between university and organization. In the Literature Review it was approached the relationship between university and organization; the curricular training in Brazil; the agents involved in the process of curricular training, with the emerging of the integration agent and the university; and the Brazilian industry, which was the first segment to offer vacancy of curricular training, and the worker formation; and the organizational management. The method adopted for the accomplishment of the research is the Case Study of IEL/Bahia, in the city of Salvador, where its headquarters is located, as a result of the author of the study being manager of interaction university-organization of the institute, being her main activity the intermediation of the supervised training of students in the organizations. The primary source of data had been obtained during the months of April and May of the current year, through interviews semi structured, directed to the representatives of the human resources area of conceding organizations and professors of the training disciplines in institutions of higher education, and questionnaires answered by students who are going through the curricular training. Secondary sources of data were formed by participant observation and documentary analysis, composed by the evaluation of written materials such as: laws, regulations, norms, letters, memorandums, periodicals, magazines, speeches, scripts of radio programs and television, books, statistics results and archives. From the data, it was concluded that the integration agent can contribute to the improvement of the curricular training s quality, through the expansion of its performance together with the conceding units.